Changes in plasma membrane fluidity lower the sensitivity of S. cerevisiae to killer toxin K1 - Flegelová, H; Chaloupka, R; Novotná, D; Malác, J; Gásková, D; Sigler, K; Janderová, B (Folia microbiologica, 2003)
The possible correlation between plasma membrane fluidity changes induced by modified cultivation conditions and cell sensitivity to the killer toxin K1 of Saccharomyces cerevisiae were investigated. Cells grown under standard conditions exhibited high toxin sensitivity. Both a membrane fluidity drop and fluidity rise brought about markedly reduced sensitivity to the toxin. These results do not fit the hypothesis of physiological relevance of direct toxin-lipid interaction, suggesting that the essential event in killer toxin action is interaction with membrane protein(s) that can be negatively influenced by any changes of membrane fluidity.
Keywords: Temperature; Culture Media; Fluorescent Dyes; Mycotoxins; kultivační média; Saccharomyces cerevisiae; Diphenylhexatriene; antiinfekční látky lokální; Cell Membrane; Fatty Acids, Unsaturated; fluidita membrány; difenylhexatrien; Ethanol; ethanol; buněčná membrána; fluorescenční barviva; Anti-Infective Agents, Local; Killer Factors, Yeast; Membrane Fluidity; teplota; nenasycené mastné kyseliny; killer faktory kvasinek; mykotoxiny